2006
DOI: 10.1214/ejp.v11-377
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic Behaviour of the Simple Random Walk on the 2-dimensional Comb

Abstract: We analyze the differences between the horizontal and the vertical component of the simple random walk on the 2-dimensional comb. In particular we evaluate by combinatorial methods the asymptotic behaviour of the expected value of the distance from the origin, the maximal deviation and the maximal span in n steps, proving that for all these quantities the order is n 1/4 for the horizontal projection and n 1/2 for the vertical one (the exact constants are determined). Then we rescale the two projections of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 17 publications
0
32
0
Order By: Relevance
“…For random walk on comb we refer to Weiss and Havlin [29], Bertacchi and Zucca [2] and references given there. The following result on weak convergence was established by Bertacchi [1].…”
Section: The Case α =mentioning
confidence: 93%
“…For random walk on comb we refer to Weiss and Havlin [29], Bertacchi and Zucca [2] and references given there. The following result on weak convergence was established by Bertacchi [1].…”
Section: The Case α =mentioning
confidence: 93%
“…A further insight to the nature of the random walk on a comb was provided by Bertacchi [2], who established the following remarkable weak convergence result for the walk C(n) = (C 1 (n), C 2 (n)) on the comb C 2 .…”
Section: Consequence 23mentioning
confidence: 99%
“…Now, just like as it is used in [2], we may apply the Hardy-Littlewood-Karamata theorem in the following form: If…”
Section: Remark 22mentioning
confidence: 99%
“…This is a rather surprising phenomenon, in view of the fact that the random walk is recurrent, that is, a single random walker visits each site an infinite number of times with probability 1. Some insight was provided by Bertacchi and Zucca [BeZ03] and by Bertacchi [Be06], whose asymptotic estimates suggested that a walker spends most of her time moving vertically along a "tooth" of the comb. Several strong approximation and limit theorems for random walks on a comb have been established by Csáki, Csörgő, Földes, and Révész [CsCs09], [CsCs11].…”
Section: Introductionmentioning
confidence: 99%
“…According to the main result in [WeH86], the expected value of V n is asymptotically proportional to n 3/4 , for large n. It is not hard to see that almost surely the deviation of the horizontal projection X n of the walk is roughly n 1/4 , while the expected length of the vertical projection is of order n 1/2 . See, e.g., Bertacchi [Be06] (cp. Panny and Prodinger [PaP85]).…”
Section: Introductionmentioning
confidence: 99%